2017
DOI: 10.15171/jrip.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

Multicystic dysplastic kidney and related epidemiologic factors

Abstract: Better understanding of conditions that predispose MCDK could be a critical step towards improving clinical consequence and management of this disease. Since there is little evidence on the relationship between MCDK and epidemiologic factors, we evaluated this relationship hypothesizing that these epidemiologic conditions would increase the risk of MCDK. Please cite this paper as: Introduction:Multicystic dysplastic kidney (MCDK) is a sporadic developmental abnormality caused by abnormal differentiation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The metanephros is the final stage that produces the permanent kidney from the 5th week of embryonic development. Failure of metanephric differentiation, as well as the branching of the ureteric bud into the collecting ducts and ureter at this stage [4], leads to the sporadic congenital malformation called multicystic dysplastic kidney (MCDK) consisting of multiple, noncommunicating cysts along with immature, undifferentiated and primitive or dysplastic tissue [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…The metanephros is the final stage that produces the permanent kidney from the 5th week of embryonic development. Failure of metanephric differentiation, as well as the branching of the ureteric bud into the collecting ducts and ureter at this stage [4], leads to the sporadic congenital malformation called multicystic dysplastic kidney (MCDK) consisting of multiple, noncommunicating cysts along with immature, undifferentiated and primitive or dysplastic tissue [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…[ 101 ] The results of research have confirmed that this plant extract causes inhibition of cancer cells AGS level. [ 102 103 104 105 106 ] Table 3 refers the most important medicinal plants with anticancer of different lines such as AG (stomach adenocarcinoma).…”
Section: The Anticancer Effect Of Medicinal Plants and Their Effectivmentioning
confidence: 99%